A rare case of malignant meningitis from a likely bronchogenic melanoma primary cancer. Issue 1 (24th January 2019) - Little, Jessica; Rajkumar, Christopher; Saleem, Waqar
Abstract: Malignant meningitis is a rare condition with varied clinical presentations, often mimicking other neurological conditions. Here we report a rare case of malignant meningitis from primary bronchogenic melanoma. The patient initially presented with vomiting and headache. Over the next 12 days she developed rapidly progressive neurology: losing mental faculties, vision, hearing and limb power. Lumbar puncture results revealed malignant cells. Computer tomography of the chest found an endobronchial lesion which was later biopsied and histology revealed a melanoma. This condition is very rare and diagnosis was difficult. We discuss ideas to help expedite diagnosis and management of such cases in the future.